Laboratory Results and Clinical Characteristics of Probable Omicron Patients at Dr. Wahidin Sudirohusodo Hospital - Fadhlan Fadhlan; Uleng Bahrun; Tenri Esa (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Since the Omicron variant was first detected on November 24, 2021, in Southern Africa, it has now been detected in more than 110 countries and is estimated to continue to spread. Given the rapid spread and serious dangers of COVID-19, it is urgent to continuously improve and expand research on its clinical diagnosis and treatment. The analysis of this study identifies the laboratory results and clinical characteristics of probable Omicron. This study aimed to determine the laboratory results and clinical characteristics of probable Omicron patients at Dr. Wahidin Sudirohusodo Hospital. This descriptive study used a cross-sectional approach with medical record data of probable Omicron patients at Dr. Wahidin Sudirohusodo Hospital from January to July 2022 with a total of 241 research subjects. The results of the analysis showed that probable Omicron patients at Dr. Wahidin Sudirohusodo Hospital who were hospitalized consisted of 124 (51.5%) males and 117 (48.5%) females, 66 (22.8%) subjects with age range >60 years, 88 (30.4%) subjects with age range of 40-60 years, 45 (15.6%) subjects with age range 19-40 years and 42 (14.5%) subjects with age <18. Most subjects, which consisted of 79 (27.3%) patients reside in Makassar. The mean WBC count, NLR value, LMR value, and CT value found in this study were 10.8; 5.6; 0.5; and 33.94, respectively. The Omicron variant infects more males than females mainly at the age of 40-60 years, with a relatively low average CT value of 33.94 and a slight increase of NLR, MLR, and WBC count.